Os ciberconsumidores e a ciberpublicidade: marcação interagente e interações reativas como práticas de consumo no facebook - SOUSA, Thatianne Silva (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
In this article, we present reflections about consumer practices developed by cyberconsumers from the way they interact with (and from) ciberpublicity on social networks on the Internet, specifically on Facebook. A brief theoretical approach on the concepts of cyberpublicity and the role of cyberconsumers, we describe the methodological course that helped us in the analysis of interactions and in the identification of cultural and media consumption practices that we call interagent tagging and reactive symbolic interaction.